Highly Sensitive and Rapid Identification of Streptococcus agalactiae Based on Multiple Cross Displacement Amplification Coupled With Lateral Flow Biosensor Assay - Cheng, Xueqin; Dou, Zhiqian; Yang, Jing; Gu, Yulong; Liu, Dexi; Xie, Ling; Ren, Tao; Liu, Yan; Yu, Zhifang; Tang, Yijun; Wang, Meifang (Frontiers in Microbiology, 2020)
Streptococccus agalactiae(S. agalactiae) is an important neonatal pathogen that is associated with obvious mortality and morbidity. Therefore, we developed a rapid, accurate and sensitive method on the basis of multiple cross displacement amplification (MCDA) for the target pathogen detection. Four sets of MCDA primers were designed targeting S. agalactiae-specific groEL gene, and one set of MCDA primers with the optimum amplification efficiency was screened for establishing the S. agalactiae-MCDA assay. As a result, the new developed assay could be conducted at a fixed temperature (61 °C) for only 30 min, eliminating the use of complex instruments. Particularly, an easy-to-carry and user-friendly nanoparticles-based lateral flow biosensor (LFB) assay was employed for reporting MCDA results within 2 min. Our result suggested that the detection limit of the S. agalactiae-MCDA-LFB assay is 300 fg per reaction, and no cross-reaction occurred with non-S. agalactiae strains. For 260 vaginal and rectal swabs, the detection rate of the MCDA-LFB assay was 7.7%, which was in accordance with the reference method of enrichment/qPCR, and higher than 3.1% by CHROMagar culture. Moreover, the total procedure time of the MCDA-LFB assay was around 50 min, including sample collection, template preparation, MCDA reaction and result reporting. Therefore, the MCDA-LFB assay is superior to enrichment/qPCR and CHROMagar culture, and has great promise for point-of-care test of S. agalactiae from vaginal and rectal swabs of pregnant women at resource-limited settings.